2009
DOI: 10.1590/s1516-35982009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Seed controlled deterioration of three interspecific elephant grass × pearl millet hybrids

Abstract: -In order to allow using seeds from three interspecific elephant grass × pearl millet hybrids (Original, Cutting Palavras-chave: equação de viabilidade, Pennisetum purpureum × P. glaucum, seleção recorrente

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Butler et al [18] applied probit analysis for Digitalis purpurea and Soltani [19] tested with Haloxylon persicum. Pozitano and Usberti [20] obtained good relationship for controlled deterioration in grass seeds, using the theory of probit analysis and Surki et al [21] applied for soybean viability. Babiker et al [22] concluded that controlled conventional drying process resulted in better viability, compared to alternative methods, such as silica-gel or sun drying.…”
Section: Introductionmentioning
confidence: 99%
“…Butler et al [18] applied probit analysis for Digitalis purpurea and Soltani [19] tested with Haloxylon persicum. Pozitano and Usberti [20] obtained good relationship for controlled deterioration in grass seeds, using the theory of probit analysis and Surki et al [21] applied for soybean viability. Babiker et al [22] concluded that controlled conventional drying process resulted in better viability, compared to alternative methods, such as silica-gel or sun drying.…”
Section: Introductionmentioning
confidence: 99%